Interpreting Solomon in colonial and post-colonial Africa - Holter, Knut (Old Testament essays, 2006)
The article analyses two sets of cases of how the Old Testament tradition about King Solomon has been interpreted in Africa. The first set dates back to colonial times and exemplifies how the Solomon tradition was linked to the discovery of Great Zimbabwe, in order to provide a biblical counterpart to the colonization of Africa. And the second set exemplifies how contemporary historical-critical Old Testament scholarship in Africa still reflects a hermeneutic framework of colonialism.